PROBLEM DAN TANTANGAN PUSKESMAS DAN RUMAH SAKIT UMUM DAERAH DALAM MENDUKUNG SISTEM RUJUKAN MATERNAL DI KABUPATEN KARIMUN PROVINSI KEPRI TAHUN 2012 - Siti Noor Zaenab, Zulhadi Laksono Trisnantoro (Jurnal Kebijakan Kesehatan Indonesia, 2013)
Background: Strengthening referral system is a method toaccelerate decrease of maternal mortality rate. The main factorsaffecting referral system are facilities, staff, team work, andbudget that need seroius attention from all stakeholdersinvolved in the program of maternal health. By strengtheningthe system of maternal health the problem and the challenge ofhealth center to support of maternal referral can be addressed.Objective: The study aimed to evaluate referral system ofmaternal health at District of Karimun Province of KepulauanRiau.Method: This was a qualitative case study undertaken atKarimun Hospital and 2 health centers with high maternal andinfant mortality rate, i.e. Meral and Moro Health Center thatwere located at both urban and rural areas. Data were obtainedthrough in-depth interview, focus group discussion,observation, checklist and document study.Result: The result of the study showed there was limitation ofresources at primary health service such as facilities andequipments and hospital limited ability to provide comprehensiveemergency neonatal and obstetric management despite beingoperated 24 hours. There were lack of team coordicationacross referral levels involving district health office, hospitaland health centers, incomplete standard operating procedures,weak information system and bypassing referral procedure.Community participation in referral system was very highthough some labor was assisted by traditional childbirthattendants. This condition was mainly due to cultural factors/reasons.Conclusion: There are some problems and challenges in bothprimary health service and hospitals to support maternalreferral system in Karimun District. Some policies are requiredas a first step toward better referral system in Karimun District,for instance accelerating a functioning CMOC hospital,strengthening the teamwork across referral system, andestablishing SOP for maternal cases including its referralprocedures.Keywords: Problem, Challenge, Maternal referral system,Health Center, Distric Goverment Hospital.